OPEN ANTERIOR CORDOTOMY AS A POSSIBLE TECHNIQUE FOR PAIN RELIEF IN CANCER PATIENT: AN EXPERIENCE WITH SEVEN CASES - Sheikhrezai; A.; Tabatabai; A Hussain Khan; Z. (Acta Medica Iranica, 1996)
Seven patients who had intractable pain of the pelvis and lower extremities were scheduled for cordotomy of the spinothalamic tracts after preliminary investigations. In three patients laminectomy was performed, to approach the anterior portion of the spinal cord, anil in the rest anterior cordotomy was performed with anterior disectomy under direct vision of the spinal cord. It appears that anterior approach is an alternative technicque for anterior cordotomy in some patients.